A new non-divergence diffusion equation with variable exponent for multiplicative noise removal. (December 2020) - Shao, Jingfeng; Guo, Zhichang; Shan, Xiujie; Zhang, Chao; Wu, Boying
Abstract: A new kind of model based on double degenerate parabolic equation in nondivergence form is proposed for multiplicative noise removal. We first utilize the regularization method to illustrate the existence of the weak solution for the problem and the non-expansion of support of the solution is also provided. In the numerical aspect, experiments and comparisons with other denoising models are presented in order to state the denoising capability of our model.